Application of chromato-mass spectrometry to determine the acid composition of transformer oil - M. N. Lyutikova; S. M. Korobeynikov; A. V. Ridel (Омский научный вестник)
This article presents the results of a study of the acid composition of transformer oil from high-voltage transformers that have been in operation for more than 30 years. The acid composition of oils is studied using a new technique based on a highly sensitive and highly selective analysis method — chromato-mass spectrometry. The technique makes it possible to determine the acid composition of the insulating oil in the context of low molecular weight acids (LMA), high molecular weight acids (HMA) and phenolic compounds (PC). The structure of some compounds identified in oil is given. It has been established that during oil aging, among the acid compounds, the following are predominantly formed: HMA (60–95 %) > PC (3–16 %) > LMA (1–6 %). As part of the research, it is found that the share of the most dangerous low molecular weight acids in the total amount of acidic compounds is no more than 12 %. The rest of the acidity of the oil is due to the presence of macromolecular and phenolic compounds, which do not adversely affect the insulating properties of oil and paper in the detected concentrations, and some of them (compounds of a phenolic nature), on the contrary, even improve the stability against oxidation. These extended tests of oil samples from operating high-voltage equipment are of practical value in preventive diagnostics of the condition of its insulation.